Determinants of financial inclusion and their impacts on income inequality and poverty - Rasheed, Balach (2017)
This thesis aims to examine the determinants of financial inclusion and its impact on income inequality and poverty. The first objective of the study is to examine the effect of culture and the gender gap on financial inclusion. The second objective of the study is to investigate role of financial inclusion in moderating remittances on income inequality. Lastly, we evaluate the role of institutional quality in moderating financial inclusion and poverty. There are other studies on the determinants of financial inclusion; however, this study seeks to examine the link between financial inclusion and culture. Financial exclusion is divided into voluntary and involuntary financial exclusion (World Bank, 2014). Voluntary financial exclusion is the segment of the population which decides not to use formal financial institutions because of some cultural barrier. For example, citizens may be excluded by language or by religious teachings. In addition, certain societies may obstruct women to utilise formal financial institutions. Therefore, this study aims to examine the effects of culture and gender gap on financial inclusion. It uses system generalised method of moments (system GMM) on a group of 94 countries during the 2004-2013 period. The findings demonstrate that the impact of the gender gap and culture are positive and significant for financial inclusion when the culture is Catholic and Protestant, whereas for the Muslim culture it shows a negative effect but insignificant. This study also includes the interaction between cultural proxies and the gender gap in influencing financial inclusion. The interaction between cultural proxies and the gender gap for Catholic and Protestant population countries suggest that gender equality tends to significantly increase financial inclusion. By contrast, Muslim population countries have a negative but insignificant coefficient. There are various gaps in existing literature related to financial inclusion, remittances and income inequality. First, evidence on the interaction between financial inclusion and remittances is highly inconclusive. Second, income inequality has not yet been explored with regards to the financial inclusion-remittance link. Third, past studies have failed to investigate the group of 90 countries for the recent period of 2004-2013 with respect to financial inclusion-remittance link. To link and complete the current gaps in the literature, the second objective of study is to investigate the role of financial inclusion in moderating remittances on income inequality. Remittances and financial inclusion have a significant negative effect on income inequality. The estimated results found a non-linear relationship between GDP per capita and income inequality. The interaction between remittance and financial inclusion has a negative relationship with income inequality. Thus, higher remittances increase the level of financial inclusion and hence a reduction in income inequality. The last objective of this thesis is to contribute to the literature by examining the role of institutional quality in the financial inclusion and poverty nexus. This is motivated by the widely accepted view that financial inclusion can contribute to financial growth and poverty reduction. Therefore, to sustain modern development theory we can express that better financial inclusion reduce poverty if there is strong institutional quality. This objective used system GMM in a group of 87 countries during the 2005- 2012 period. The coefficient of the interaction term between financial inclusion and institutional quality is negative and significant, suggesting that stronger institutions further enhance the role of financial inclusion and thus reduce poverty.